Paleoindian Aggregation and Social Context at Bull Brook. Issue 3 (20th July 2009) - Robinson, Brian S.; Ort, Jennifer C.; Eldridge, William A.; Burke, Adrian L.; Pelletier, Bertrand G.
Abstract : Large social aggregations are among the most highly organized events associated with mobile hunter-gatherers. The Bull Brook Paleoindian site in Ipswich, Massachusetts provides the strongest case for large-scale Paleoindian aggregation in North America, with 36 discrete concentrations of artifacts arranged in a large circle. Avocational archaeologists who salvaged the site in the 1950s interpreted it as a single occupation. Professionals first rejected and then revived this hypothesis, but the site remained insufficiently analyzed to evaluate. New research supports the single occupation hypothesis with a fully reconstructed site plan and the first complete analysis of artifact distributions. Clear spatial structure of activities within the ring-shaped site plan provides a window on social contexts that are also visible in smaller Paleoindian settlements.